Peningkatan Keterampilan Berhitung Perkalian dan Pembagian Melalui Kegiatan Bimbingan Belajar Matematika dengan Metode Ekspositori: Sebuah Program Pengabdian Masyarakat - Fitriana Aulia Sabila Eka Putri; Yani Rahmawati (Direktorat Pengabdian kepada Masyarakat, 2026)
Education supports national development when students and graduates develop and apply their knowledge and capabilities to solve their daily problems. One field of expertise used in daily life is mathematics. According to the established competency standards, elementary school graduates are expected to master multiplication and division. However, based on the preliminary surveys conducted at MI Ma’arif Giriloyo 1 and 2, the school principals reported that many students still struggling with both mathematical operations. To address this issue, undergraduate students conducted a community service program by providing required training for fifth-grade students at MI Ma’arif Giriloyo 1 and 2, utilising an expository approach. A quantitative descriptive analysis with a one-group pretest-posttest design was used to measure the impact of the effort. The questionnaire was validated through discussions with experts, specifically the fifth-grade teachers at MI Giriloyo 1 and 2. The sample consisted of 97 elementary students. Normality tests using the Shapiro-Wilk test followed by the Wilcoxon statistical test revealed an overall increase in the mean posttest scores in mathematics (84.62) compared to the pretest scores (75.97), with an improvement of 8.65% after the tutoring intervention. However, the Wilcoxon test results showed that the Negative Ranks were higher than the Positive Ranks (21.72 > 18.81), and posttest scores declined among nine students. These changes in posttest scores were statistically significant. Considering the data context, where the Positive Rank = 18.81 and the Negative Rank = 21.72, it can be interpreted that the median data tends to decline because the average negative rank is larger, and this difference is statistically significant (p = 0.010). Therefore, it can be concluded that the mathematics tutoring program was still effective in improving the multiplication and division skills of fifth-grade students at MI Giriloyo 1 and 2.